Do polluting enterprises contribute to cancer?—Empirical evidence from tumor registry data in China - Jiwen Liu; Bingquan Lin; Bingquan Lin (Frontiers in Public Health)
This study utilizes data from the China Cancer Registry Annual Report and the “Qichacha” database to construct a time-region regression model based on panel data, aiming to explore the impact of polluting enterprises on regional cancer incidence rates between 2000 and 2008. The empirical analysis reveals that polluting enterprises significantly increase cancer incidence rates among both male and female populations, with a particularly marked effect on lung cancer. Heterogeneity analysis shows that the effect is most pronounced in the eastern and coastal regions, followed by the central and northeastern areas, with minimal impact in the western and inland regions. There may be a threshold effect in the influence of polluting enterprises on cancer incidence. Additionally, local government environmental regulations can mitigate the negative health impacts of industrial pollution. Mechanism analysis indicates that polluting enterprises influence regional public health through environmental pollution, while also highlighting potential disparities in urban-rural medical compensation. The findings provide empirical support and mechanism validation for understanding the impact of polluting enterprises on public health, offering valuable insights for the “Healthy China” strategy and environmental governance policies.